Gender gap in Acquisition and practice of Agricultural Knowledge: Case study of Rice Farming in West Africa - Zossou, E.; Arouna, A.; Diagne, A.; Agboh-Noameshie, A.R. (Cambridge University Press, 2017)
Improving farmers’ knowledge of new technologies and creating conducive learning opportunities, with particular attention to the marginalized poor (women and youth), are major factors in the move towards sustainable agriculture. To explore the gender gap in agricultural knowledge acquisition and adoption in West Africa, we used baseline data collected in 2013 and 2014 in five countries (Benin, Côte d'Ivoire, Niger, Nigeria and Togo) with 499 surveyed households. The t-test and Kruskal–Wallis test were used for analysis. The most quoted source for acquiring knowledge on rice farming methods was ‘other farmers’, showing the importance of social capital for rural African farmers. In Benin, a gender gap was noted in rice farmers’ access to agricultural knowledge sources, with women being more advantaged. In Côte d'Ivoire, Niger, Nigeria and Togo, no significant gender gap was observed in rice farmers’ access to agricultural knowledge sources. Regarding the level of knowledge and use of rice farming methods in Côte d'Ivoire and Niger, significant gender gaps were observed. The gender approach to rural development is having impact in West Africa with regard to farmers’ access to agricultural information. However, interactive rural learning approaches (such as farmer-to-farmer video) need to be resorted to make the technologies’ principles well known and improve the ability of marginalized poor to adopt and or innovate with local or limited resources. This study leads to a better understanding of the relationship between gender, knowledge and use of agricultural technologies in order to enhance marginalized farmers’ adoption of improved innovations.